Jacket Structure’s Responses due to Ship Collision - Sumiwi, Agustin Dwi; Afrizal, Efi; Junaidi, Abd Khair (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2014)
Jacket structure is affected by fluid load or external load when it operationed. One of external load that affect it is impact load subject to something collision. This examination talked about graded and velocity supply vessel influence to local and global structure damage subject to collision. Jacket structure in this examination is CONOCO BELANAK wellhead plaform, mass of supply vessel is 2500 tonnes, with tidal variation (such as: MSL, HWL, LWL) for scenario sideway and stern/bow impact for each normal and 10% exceedane velocity. Deformation type of landing platform impact load is dent subject to landing platform material unability to proof againts pressure. This examination refers to J.P. Kenny in 1988 with title Protection of Offshore Instalasions agains Impact. This examination uses 2 software are ANSYS LS-DYNA 9.0 version and GT-STRUDL 27.0 version. First of all, modeling geometry and loading in ANSYS LS-DYNA to acquired local deformation. Than modeling jacket structure in GT-STRUDL to acquired global deformation uses dynamic trancient analysis. Outside diameter of landing platform is 0.9144 m with wall thickness is 0.0381 m. Normal velocity in each sideway and stern impact is and 10% exceedance velocity is 0.28 m/s and 0.39 m/s. 10% exceedance velocity in each sideway and stern impact is and 10% exceedance velocity is 0.54 m/s and 0.73 m/s. The resutl of this examination is dent of landing platform for each normal and 10% exceedance is 0.2725 m and 0.2352 m, it must be repaired or changed because of it is 10% larger than spacing frame. Maximum displacement x, y, z direction is 0.2423 m on 0.38 s, 0. 0559 m on 0.39 s, 0.7492 m on 0.41 s. The deformation in landing platform and jacket structure is smaller than examination result indeed.